Chiral macrocyclic terpyridine complexes. Issue 15 (3rd April 2018) - Brandl, Thomas; Hoffmann, Viktor; Pannwitz, Andrea; Häussinger, Daniel; Neuburger, Markus; Fuhr, Olaf; Bernhard, Stefan; Wenger, Oliver S.; Mayor, Marcel
Abstract : Interlinking of two terpyridine ligands results in mononuclear chiral metal complexes (Fe and Ru) which were separated into their enantiomers. Abstract : The syntheses of novel chiral M(ii ) bis(terpyridine) cage complexesFe(L1)2 -c andRu(L1)2 -c are described. The extraordinary design of the precursorsFe(L1)2 andRu(L1)2 allows perfect preorganization for the final closing step. Due to the rigidity of the spacers between the two terpyridine moieties, the two isolated enantiomers barely racemize at room temperature in solution. The stable and axially chiral bis(terpyridine) Fe(ii ) and Ru(ii ) complexes were fully characterized by NMR-spectroscopy, UV-Vis spectroscopy, electrochemical measurements, high resolution mass spectrometry, circular dichroism measurements, and X-ray structural analysis.